Analysis of Community Oil Palm Plantation Management in Nagari Sitiung District, Sitiung, Dharmasraya Regency - Maina Roza; Nefilinda Nefilinda; Slamet Rianto (Universitas Lambung Mangkurat, 2025)
This study aims to analyze the management of oil palm plantations by the community in Nagari Sitiung, Sitiung District, Dharmasraya Regency. The study concentrated on three principal dimensions: land planning and selection, accessibility to facilities and infrastructure, and environmental degradation resulting from oil palm plantations in Nagari Sitiung. The research method used was descriptive quantitative research, with data collected through observation, interviews, and questionnaires distributed to 100 respondents. The results indicated that 1) land planning and selection for oil palm plantations were carried out taking into account soil fertility, slope, water availability, and flood risk, with a Respondent Achievement Rate (TCR) of 84.62%, which is considered satisfactory; and 2) access to facilities and infrastructure was deemed adequate, including easy access to fertilizer, agricultural equipment, and road access, with a TCR of 84.18%. 3) Most farmers have abandoned the practice of land clearing by burning and prefer manual or mechanical methods, indicating an increased awareness of the negative impacts of smoke and soil degradation. However, the use of chemical fertilizers and pesticides is still very dominant because they are considered more effective and easy to obtain, while the management of harvest waste is carried out simply by leaving it on the land or making it into natural compost.